Cerebellar Oxidative DNA Damage and Altered DNA Methylation in the BTBR T+tf/J Mouse Model of Autism and Similarities with Human Post Mortem Cerebellum - Shpyleva, Svitlana (PLoS One, 2014)
The molecular pathogenesis of autism is complex and involves numerous genomic, epigenomic, proteomic, metabolic, and physiological alterations. Elucidating and understanding the molecular processes underlying the pathogenesis of autism is critical for effective clinical management and prevention of this disorder. The goal of this study is to investigate key molecular alterations postulated to play a role in autism and their role in the pathophysiology of autism. In this study we demonstrate that DNA isolated from the cerebellum of BTBR T+tf/J mice, a relevant mouse model of autism, and from human post-mortem cerebellum of individuals with autism, are both characterized by an increased levels of 8-oxo-7-hydrodeoxyguanosine (8-oxodG), 5-methylcytosine (5mC), and 5-hydroxymethylcytosine (5hmC). The increase in 8-oxodG and 5mC content was associated with a markedly reduced expression of the 8-oxoguanine DNA-glycosylase 1 (Ogg1) and increased expression of de novo DNA methyltransferases 3a and 3b (Dnmt3a and Dnmt3b). Interestingly, a rise in the level of 5hmC occurred without changes in the expression of ten-eleven translocation expression 1 (Tet1) and Tet2 genes, but significantly correlated with the presence of 8-oxodG in DNA. This finding and similar elevation in 8-oxodG in cerebellum of individuals with autism and in the BTBR T+tf/J mouse model warrant future large-scale studies to specifically address the role of OGG1 alterations in pathogenesis of autism.